When Stakeholder Representation Leads to Faultlines. A Study of Board Service Performance in Social Enterprises - Crucke, Saskia; Knockaert, Mirjam (Journal of Management Studies, 2016)
AbstractFollowing the growing interest in sustainability and ethics, organizations are increasingly attentive to accountability toward stakeholders. Stakeholder representation, obtained by appointing board members representing different stakeholder groups, is suggested to be a good ethical practice. However, such representation may also have nefarious implications for board functioning. Particularly, it may result in strong faultline emergence, subsequently mitigating board performance. Our study aims at understanding the process through which faultlines affect board performance, and particularly the board service role through which the board is involved in providing counsel and strategic decision‐making. We study the relationship between faultlines and board service performance in the particularly relevant context of social enterprises. We find that faultline strength is negatively related to board service performance and that this relationship is mediated by board task conflict. Furthermore, our study reveals the importance of clear and shared organizational goals in attenuating the negative effects of faultlines.